Waterbirds of Sardinia (Italy): How Space and Time Shape a Threatened Metacommunity During the Critical Summer Period - Alessandro Ferrarini; Marco Gustin; Claudio Celada (Land, 2024)
The wetlands of Sardinia (Italy) supply food and shelter for many waterbird species that migrate along the central–eastern Mediterranean bird flyway. Despite many different policies and laws (the Birds and Habitats Directives, the European Water Framework Directive, and the Ramsar Convention), the Sardinian wetlands are seriously threatened by human activities and climate change, which in turn menace the associated avifauna. In this study, we (a) inventoried (four sampling dates) the avian metacommunity of the largest coastal wetlands in Sardinia during the crucial period of the year for the avifauna (August–September), (b) explored the spatiotemporal dynamics in bird species assemblage, and (c) used results to refine planning for bird habitat management and bird diversity conservation. We recorded 60 bird species, of which 54 were migratory and 21 belonged to Annex I of the Birds Directive. During August–September, (a) α, β, and γ avian diversity showed no significant temporal trends, (b) the contributions of space (wetlands) and time (dates of sampling) in determining the presence/absence of the waterbird species were comparable, (c) wetlands formed three statistically significant clusters with regard to the species richness, (d) a significant increase in the number of the species belonging to the “mixed” migration guild, and “divers from the surface” foraging guild, occurred, (e) there was a statistically significant chronological succession of the occurrence of waterbird species, (f) twenty-five species made use of the Sardinian wetlands all summer long, while ten further species were present in three sampling dates out of four, (g) the spatial distributions of the waterbird species in the Sardinian wetlands were significantly different between the sampling dates, (h) the Little Egret, the Grey Heron, and the Greater Flamingo were primarily responsible for the observed difference in the spatial distributions of species between the sampling dates, (i) Is Brebeis, Pilo, and S. Giovanni were the wetlands that changed their species composition the most during the studied period, (j) twenty-two waterbird species resulted at high priority for conservation, and thirteen species at medium priority. Based on these results, we have proposed new strategies for the conservation of the waterbird species of the Sardinian wetlands during the post-breeding migration period.